Al-Lughah al-Arabiyyah wa Atsaruha fi Shiyagh Mushthalahat al-Iqtishad al-Islamy bi Indunisiyya - Abdul Fatakh; Pradi Khusufi Syamsu (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
Language is a communication tool that is used by every human being to convey a particular purpose. Arabic is recorded as having crossed the boundaries of space and time which makes it have a role in many joints of human life including the economic joints. Apart from Arabic as a language of revelation whose truth is taken for granted, it is also seen as important by the world and is one of the official languages of the United Nations (UN). Furthermore, the progress of the Islamic economy in Indonesia is strongly influenced by Arabic. Not a few Arabic terms become Islamic economic terms in Indonesia. Departing from that perspective, this article tries to describe the influence of Arabic in the formation of Islamic economic terms in Indonesia.Â